2009
DOI: 10.1111/j.1749-4486.2009.01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical procedures and non‐surgical devices for the management of non‐apnoeic snoring: a systematic review of clinical effects and associated treatment costs

Abstract: How to obtain copies of this and other HTA Programme reports. An electronic version of this publication, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable CD-ROM is also available (see below).Printed copies of HTA monographs cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our Despatch Agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…A further advantage of the one‐off component of surgery relates to costs, because the costs of CPAP, estimated in the United Kingdom as £20,000 (roughly US$30,000) per quality‐adjusted life year, typically are lifelong . Main et al published a meta‐analysis of 30 randomized, cross‐over, and other controlled clinical trials, as well as certain eligible pre‐ and post‐treatment studies, specifically comparing the costs of nonsurgical (CPAP, mandibular advancement splints, and tongue‐retaining devices) versus surgical treatment of OSA . though they admitted that data were scarce, the authors estimated that, in the United Kingdom, the average cost of a UPPP procedure at the time was £1,230 to £1,550, depending on the length of hospital stay (1 vs. 2 nights) versus £220 annually for CPAP, meaning that the costs associated with CPAP would start to exceed those of surgery within 6 to 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…A further advantage of the one‐off component of surgery relates to costs, because the costs of CPAP, estimated in the United Kingdom as £20,000 (roughly US$30,000) per quality‐adjusted life year, typically are lifelong . Main et al published a meta‐analysis of 30 randomized, cross‐over, and other controlled clinical trials, as well as certain eligible pre‐ and post‐treatment studies, specifically comparing the costs of nonsurgical (CPAP, mandibular advancement splints, and tongue‐retaining devices) versus surgical treatment of OSA . though they admitted that data were scarce, the authors estimated that, in the United Kingdom, the average cost of a UPPP procedure at the time was £1,230 to £1,550, depending on the length of hospital stay (1 vs. 2 nights) versus £220 annually for CPAP, meaning that the costs associated with CPAP would start to exceed those of surgery within 6 to 7 years.…”
Section: Discussionmentioning
confidence: 99%
“…This is an attractive concept as these recreational activities are safe, cost‐effective and potentially enjoyable in their own right. Existing treatments have significant drawbacks in terms of efficacy, cost and morbidity 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…concluded that Pillar implants, which are designed to be inserted into the soft palate to reduce vibration and collapsibility, were efficacious in significantly reducing bed‐partner‐assessed snoring sound in patients with snoring, and in patients with mild‐to‐moderate obstructive sleep apnoea significantly reduced the Epworth Sleepiness Scale score and apnoea–hypopnoea index. A systematic review of 27 studies of overwhelmingly level III evidence demonstrated that in patients with non‐apnoeic snoring uvulopalatopharyngoplasty, laser‐assisted uvulopalatoplasty, radiofrequency ablation of the soft palate and Pillar implants were all associated with a significant reduction in patient or bed‐partner‐reported snoring levels . Another systematic review of 49 clinical studies of multi‐segmental surgical interventions, defined as involving at least two of the frequently involved anatomical sites (nose, oropharynx and/or hypopharynx) in adults with obstructive sleep apnoea, demonstrated improved outcomes in terms of reduction in apnoea–hypopnoea index, but this benefit was predominantly from level III evidence …”
Section: What Further Investigations or Management Should You Offer?mentioning
confidence: 99%